Parental investments and children's human capital in low-to-middle-income countries - Behrman, Jere Richard, 1940- (Cambridge : Cambridge University Press, 2022)
This Element reviews what we know about parental investments and children's human capital in low-to-middle-income countries (LMICs). First, it presents definitions and a simple analytical framework; then discusses determinants of children's human capital in the form of cognitive skills, socioemotional skills and physical and mental health; then reviews estimates of impacts of these forms of human capital; next considers the implications of such estimates for inequality and poverty; and concludes with a summary suggesting some positive impacts of parental investments on children's human capital in LMICs and a discussion of gaps in the literature pertaining to both data and methodology. This title is also available as Open Access on Cambridge Core.
Title from publisher's bibliographic system (viewed on 10 Nov 2022).
Keywords: Parenting -- Developing countries; Parent and child -- Developing countries; Children -- Developing countries -- Social conditions; Children -- Developing countries -- Social life and customs; Social learning -- Developing countries